CORPORATE PROFITABILITY, AUDIT QUALITY & BOARD GENDER DIVERSITY: DOES IT INFLUENCE TAX AVOIDANCE? - Amanda, Reika Alicya; Fitriana, Vita Elisa; Mapuasari, Supeni Anggraeni (Ultimaccounting Jurnal Ilmu Akuntansi, 2023)
Abstract - This study aims to determine the effect of company profitability and audit quality on tax avoidance, where board gender diversity will be examined as a moderating variable. Several previous studies found inconsistent results regarding the influence of each variable on tax avoidance. In addition, this study extends earlier research, which highly suggests examining the audit quality. Further, in Indonesia, there is a demand for including women in the boardroom, while the last 2 years show that women's participation is decreasing. It indicates that the variables examined are interesting to further investigate. Purposive sampling was used as the sampling method, which generated 15 companies from mining, technology, transportation, and logistics listed on the Indonesia Stock Exchange for 2019–2021. The collected data will be analyzed using moderate regression analysis (MRA). The empirical results showed that both corporate profitability and audit quality positively influence tax avoidance. However, it was observed that board gender diversity does not moderate the relationship between company profitability and audit quality on tax avoidance. These results imply that a profitable company has a relatively high tendency to do tax avoidance, but the gender diversity in the boardroom is not sufficient to influence those relationships. Whatever the gender of the board of directors and certain traits embedded in each gender classification, once they come to the work field, those differences can be neglected because of their ability to work professionally. Keywords: Audit Quality; Board Gender Diversity; Corporate Profitability; Tax Avoidance